Comparative Epidemiology of Highly Pathogenic Avian Influenza Virus H5N1 and H5N6 in Vietnamese Live Bird Markets: Spatiotemporal Patterns of Distribution and Risk Factors - Mellor, Kate C.; Meyer, Anne; Elkholly, Doaa A.; Fournié, Guillaume; Long, Pham T.; Inui, Ken; Padungtod, Pawin; Gilbert, Marius; Newman, Scott H.; Vergne, Timothée; Pfeiffer, Dirk U.; Stevens, Kim B. (Frontiers in Veterinary Science, 2018)
Highly pathogenic avian influenza (HPAI) H5N1 virus has been circulating in Vietnam since 2003, while outbreaks of HPAI H5N6 virus are more recent, having only been reported since 2014. Although the spatial distribution of H5N1 outbreaks and risk factors for virus occurrence have been extensively studied, there have been no comparative studies for H5N6. Data collected through active surveillance of Vietnamese live-bird markets (LBMs) between 2011 and 2015 were used to explore and compare the spatio-temporal distributions of H5N1- and H5N6-positive LBMs. Conditional autoregressive models were developed to quantify spatio-temporal associations between agro-ecological factors and the two HPAI strains using the same set of predictor variables. Unlike H5N1, which exhibited a strong north-south divide, with repeated occurrence in the extreme south of a cluster of high-risk provinces, H5N6 was homogeneously distributed throughout Vietnam. Similarly, different agro-ecological factors were associated with each strain. Sample collection in the months of January and February and higher average maximum temperature were associated with higher likelihood of H5N1 positive market-day status. The likelihood of market-days being positive for H5N6 increased with decreased river density, and with successive Rounds of data collection. This study highlights marked differences in spatial patterns and risk factors for H5N1 and H5N6 in Vietnam, suggesting the need for tailored surveillance and control approaches.